An Extended State Observer Based Fractional Order Sliding‐Mode Control for a Novel Electro‐Hydraulic Servo System with Iso‐Actuation Balancing and Positioning. Issue 1 (14th September 2018) - Gao, Qiang; Hou, Yuanlong; Liu, Jingbao; Hou, Runming; Lv, Mingming; Wang, Li; Wang, Chao
Abstract: An extended state observer based fractional order sliding‐mode control (ESO‐FOSMC) is proposed in this study, with consideration of the strong nonlinear characteristics of a new electro‐hydraulic servo system with iso‐actuation balancing and positioning. By adopting the fractional order calculus theory, a fractional order proportional–integral–derivative (PID)‐based sliding mode surface was designed, which has the ability to obtain an equivalent positioning control with fractional order kinetic characteristics. By introducing the integral term into the sliding mode surface, it was found to be beneficial in reducing the steady‐state errors, as well as improving the precision of the control system. Also, by using the fractional order calculus to replace the integral calculus, the form of the convergence is improved; the system transfer of energy is slowed down; and the chattering of the system is greatly weakened. The extended state observer was designed to observe the real‐time disturbances, and also to generate the compensation control commands which are added to the FOSMC to achieve the dynamic compensation. By means of numerical simulations, the dynamic and static characteristics of the sliding mode control system were compared with those of the FOSMC and ESO‐FOSMC. The experimental results show that the ESO‐FOSMC system could effectively restrain the external disturbances and achieve higher control precision, as well as better control quantity without chattering. The semi‐physical simulations based experimental tests also demonstrated that the proposed ESO‐FOSMC outperformed the FOSMC in terms of system robustness and control precision, which could have a stable control of the gun system quickly and accurately.